The Role of Active Surveillance of Papillary Thyroid Microcarcinoma: A Literature Review - Prasojo, Prasojo; Gunawan Wibisana, I Gusti Ngurah Gunawan (UI Scholars Hub, 2024)
Introduction: Thyroid cancer is one of the most common cancers in the world, with incidence 144,7: 100.000 population. The incidence has risen up to 211% within the last 30 years, and one–third of thyroid cancer is papillary thyroid microcarcinoma. There are still controversies regarding whether immediate surgery or active surveillance is the better option for treating this condition. This review aims to evaluate the safety and efficacy of active papillary thyroid microcarcinoma surveillance. Methods: Cochrane, PubMed, EBSCOHost, and ProQuest were searched for relevant studies of active surveillance of papillary thyroid microcarcinoma. Results: Six publications were selected after a literature search and review Conclusion: Active surveillance could be implemented as a treatment of papillary thyroid microcarcinoma in selected cases. The overall survival rate of papillary thyroid microcarcinoma is up to 99%, with cancer growth >3mm at 4.4% to 8%. Lymph node metastases were 1.2% to 3.8%, and distant metastases were only found in 0.04% of cases